Vocal traits of shorebird chicks are related to body mass and sex. (11th March 2022) - Kostoglou, Kristal N.; Miller, Edward H.; Weston, Michael A.; Wilson, David R.
Abstract : Acoustic communication is critical during early life phases in precocial birds; for example, adult alarm calls can elicit antipredator behaviour in young, and chick vocalizations can communicate information to parents about chick identity, condition, location, sex or age. We opportunistically recorded Red‐capped Plover Charadrius ruficapillus and Southern Masked Lapwing Vanellus miles novaehollandiae distress calls of chicks while they were in the hand and analysed the calls to determine whether call structure is related to sex or body mass (a proxy for age). Our study provides the first evidence for charadriid chicks of (1) a sexual difference in call structure and rate and (2) gradual growth‐related changes in call structure and rate, across chicks. We provide a foundation for further studies of shorebird vocalizations during growth, which may elucidate the development and functional significance of such vocalizations.